The Influence of Organizational Citizenship Behavior, Job Characteristics, Job Satisfaction and Organizational Commitment on Employee Performance in Banking Industry - Sutrisno Sutrisno; Ratih Pratiwi; Catur Sasi Kirono; Hartanto; Sunarto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of the study was to ascertain how the performance of employees of Islamic Bank was impacted by job characteristics, organizational commitment, job satisfaction, and organizational citizenship behavior. Data for this quantitative study were gathered through distributing questionnaires and using library records. This study's sample is a saturated sample. 42 people participated in the survey as responders in total. Multiple linear regression is the method of data analysis that has been applied. The study's findings revealed that organizational citizenship behavior, work happiness, organizational commitment, and job characteristics all have a major impact on how well employees of Islamic Bank perform. Additionally, this study demonstrates that organizational citizenship behavior, work happiness, organizational commitment, and job characteristics all have a substantial impact on the performance of Islamic Bank personnel. The percentage indicates that the factors of work qualities, organizational commitment, job happiness, and organizational citizenship behavior may account for 55.5% of the performance variable. While other elements or variables not included in this research account for the remaining 44.5%.